The Importance of Umbilical Blood Supply and Umbilical Delay in Secondary Abdominoplasty: A Case Report. (11th January 2018) - Parsa, Fereydoun Don; Cheng, Justin; Hu, Michael S; Kim, Leslie; Castel, Nikki; Parsa, Alan A
Abstract: The umbilicus is an important aesthetic landmark of the abdomen. It possesses a dual blood supply that allows it to survive either on its stalk if the skin surrounding the umbilicus is incised, or through the surrounding subdermal circulation if the stalk is transected. This is an important concept to consider in order to avoid umbilical ischemia and necrosis during abdominoplasty, especially if there is any past surgical history suggesting alteration to its blood supply. This case study depicts this importance and the importance of the use of delay in order to improve perfusion to the umbilicus prior to secondary abdominoplasty. In this case, a 47-year-old woman had undergone abdominoplasty two years previously and requested further improvement of her abdominal contour. At her original operation, the umbilical stalk was transected during hernia repair and the umbilicus was "floated" inferiorly to its new position. Thus, during her second revisionary abdominoplasty, it was crucial to consider the adequacy of umbilical blood supply to minimize and avoid the possibility of ischemic necrosis of the umbilicus due to alteration of umbilical blood supply. Therefore, a delay procedure of the umbilicus was performed. This case report emphasizes the need for proper consideration of umbilical blood supply, and delay of the umbilicus if alterations to its normal blood supply are known to be present or suspected to exist. Level of Evidence: 5: